Water resource management in Malaysia : legal issues and challenges. - Rahman, S.A; Khalid, R.M (WIT Press, 2009)

(untitled)
The two-wave flood incident in Malaysia in 2006 has raised concerns over the economical, sociological and psychological impact on the victims. Nevertheless, many do not realize that the tragedy has been exacerbated due to the current structure of water resource management system in the country. This paper discusses the complexities of the present legal framework with regard to water resource management in Malaysia. An examination has been made to the current Federal Constitution as well as the Federal legislations. The study proves that the problem related to water resource management in Malaysia is partly due to the unclear division of power between the Federal and the State Governments and the fragmented legislation on Malaysian water.